2016
DOI: 10.12698/cpre.2016.wp2016-8
|View full text |Cite
|
Sign up to set email alerts
|

The Bubble Bursts: The 2015 Opt-Out Movement in New Jersey

Abstract: The Bubble Bursts: The 2015 Opt-Out Movement in New Jersey analyzes the scope, factors, and context of the opt-out movement that occurred in New Jersey in the spring of 2015. Using test participation data released in February 2016 by the New Jersey Department of Education, we found that approximately 135,000 students did not take the state assessment in the spring of 2015. Depending on how it was calculated, this represented between 11-19% of the population of students eligible for testing in grades 3 to 11 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 11 publications
(11 reference statements)
1
25
0
1
Order By: Relevance
“…Opinion polls showed that, nationwide, 64 percent of people thought that children were subjected to too many standardized tests-this included strong majorities from all major demographic groups as well as diverse political affiliations (Guisbond et al, 2015). The Test Refusal Movement mushroomed, making national news and getting attention from federal and state politicians (Supovitz et al, 2016). Around the country, parents and students organized petitions, rallies, and public forums; students refused to take tests; and teachers demanded testing reform (Guisbond et al, 2015).…”
Section: A History Of the Protest Against High-stakes Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…Opinion polls showed that, nationwide, 64 percent of people thought that children were subjected to too many standardized tests-this included strong majorities from all major demographic groups as well as diverse political affiliations (Guisbond et al, 2015). The Test Refusal Movement mushroomed, making national news and getting attention from federal and state politicians (Supovitz et al, 2016). Around the country, parents and students organized petitions, rallies, and public forums; students refused to take tests; and teachers demanded testing reform (Guisbond et al, 2015).…”
Section: A History Of the Protest Against High-stakes Testingmentioning
confidence: 99%
“…In New York State, an estimated 20 percent of students refused the state exams (Buckshot, 2015). Estimates for New Jersey averaged 11 percent, with the highest rates of refusals at the high school level and in districts with higher socio-economic status (Supovitz et al, 2016). Across the country, state and local education officials reacted to try to stop the refusals, going so far as to threaten loss of funding and removal of school board members (Strauss, 2015b;Ujifusa, 2015).…”
Section: A History Of the Protest Against High-stakes Testingmentioning
confidence: 99%
See 3 more Smart Citations